2017
DOI: 10.1016/j.jpowsour.2017.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Improved supercapacitor performance of MnO2-electrospun carbon nanofibers electrodes by mT magnetic field

Abstract: This work reports on a finding of mT magnetic field induced energy storage enhancement of MnO 2 -based supercapacitance electrodes (magneto-supercapacitor).Electrodes with MnO 2 electrochemically deposited at electrospun carbon nanofibers (ECNFs) film are studied by cyclic voltammetry (CV), galvanostatic charge/discharge, electrochemical impedance spectroscopy (EIS), and life cycle stability tests in the presence/absence of milli-Tesla (mT) magnetic fields derived by Helmholtz coils. In the presence of 1.34 mT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 51 publications
3
59
0
Order By: Relevance
“…[15][16][17][18] To ensure that the fuel cell generates the maximum powero utput,a4-electron pathway (from oxygen to water) is necessary because the 2-electron pathway (from oxygen to hydrogen peroxide) involved in the cathodic process seriously compromises the energy yield of the fuel cell. [23,24] Herein, we propose an ew strategy to combinet he stable synthesis of ap aramagnetic transition metal oxide electrocatalyst and its electron transfer rate enhancement to maximize a4 -electron pathway in the ORR. [19,20] With aview to ar oute to a4 -electron pathway by effectively decomposing generated hydrogen peroxide,c atalysis by hematite nanoparticles supported on carbon nanotubes [21] or GC [22] was reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18] To ensure that the fuel cell generates the maximum powero utput,a4-electron pathway (from oxygen to water) is necessary because the 2-electron pathway (from oxygen to hydrogen peroxide) involved in the cathodic process seriously compromises the energy yield of the fuel cell. [23,24] Herein, we propose an ew strategy to combinet he stable synthesis of ap aramagnetic transition metal oxide electrocatalyst and its electron transfer rate enhancement to maximize a4 -electron pathway in the ORR. [19,20] With aview to ar oute to a4 -electron pathway by effectively decomposing generated hydrogen peroxide,c atalysis by hematite nanoparticles supported on carbon nanotubes [21] or GC [22] was reported.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, it was found that an external magnetic field over am aterial with magnetic susceptibility could facilitate the electrochemical reactions, owing to the effects of Lorentz force acting on moving charge/ions, charge density gradientm odulation, electron state excitation, and/or oscillatory magnetization. [23,24] Herein, we propose an ew strategy to combinet he stable synthesis of ap aramagnetic transition metal oxide electrocatalyst and its electron transfer rate enhancement to maximize a4 -electron pathway in the ORR.…”
Section: Introductionmentioning
confidence: 99%
“…However, poor electron conductivity limits its application into supercapacitors due to the low specific capacitance . As a typical semiconductor, manganese oxide has gained specific attention in electronic devices and supercapacitors thanks to its high bandgap, low cost, abundance, low toxicity, high theoretical capacitance (1370 F g −1 ), variable valence states, and stable chemical properties . As a typical rare earth based‐perovskite, the electrochemical behaviors of LaMnO 3 have been widely investigated owing to its stable thermal and structural properties.…”
Section: Introductionmentioning
confidence: 99%
“…CNFs are well known for their inexpensive production, freestanding nature, large porosity, and high conductivity as electrode materials for supercapacitor applications. Electrospinning, which uses electric force to draw charged threads of polymer solutions or polymer melts into nanofibers, has become an efficient fiber production method for creating porous electrospun CNFs (ECNFs) with a subsequent carbonization . Aligned ECNF structures can be used as scaffolds to uniformly support metal oxide nanoarchitectures because their alignment can significantly enhance the deposition rate by shortening the distance of electron transport.…”
mentioning
confidence: 99%